PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Hikmah Saptya Ningrum; Tri Kartika Pertiwi (Halu Oleo University, 2025)
The purpose of this study was to analyze the effect of financial ratios on stock prices with company size as a moderating variable. This study was used population includes IDX30 index companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Determination of the sample using purposive sampling technique, so that 15 companies were selected with a total of 75 data during the study period. This study was used moderation regression analysis with SPSS software version 26. The research shows the results that the liquidity ratio has a positive effect on stock prices, while the profitability ratio and leverage ratio have no effect on stock prices. Company size can moderate the relationship between liquidity ratio and stock price, but company size cannot moderate the relationship between profitability ratio and leverage ratio on stock price.